(untitled) (Public Sector Economics - submission site, 2020)
The paper analyzes fiscal effects of a Swiss-type tax on household wealth, with 120,000 exemption and marginal tax rates running from 0.05 to 0.3 percent on 2.4 million or more of wealth. It also considers a wealth tax proposed by Senator Elizabeth Warren with a 50 million exemption, a 2 percent tax on wealth above that and a 1 percent surcharge on wealth above 1 billion. Based on the 2016 Survey of Consumer Finances, the Swiss tax would yield 189.3 billion and the Warren tax 303.4 billion. Only 0.07 percent of households would pay the Warren tax, compared to 44.3 percent for the Swiss tax. The Swiss tax would have a very small effect on income inequality, lowering the post-tax Gini coefficient by 0.004 Gini points. The effect of the Swiss tax and Warren tax on wealth inequality is miniscule, lowering the Gini coefficient by at most 0.0005 Gini points.